The Economic Shock to Afghanistan Caused by Aid Reduction and Troops Withdrawal - Jawid Ahmad Nasery (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2014)
This Paper "The Economic Shock to Afghanistan Caused by Aid Reduction and Troops Withdrawal" is the first part of my M.Sc. thesis submitted to the Management and Economics Faculty of the Ruhr-University Bochum, which aims to analyze, quantify and describe the economic shock caused by the adjustments in international aid, as well as the troops withdrawal, on the Afghan economy in terms of GDP per capita growth, employment, investment and business climate and state deficit.
Keywords: 330; Afghanistan; Foreign aid; Economy; Troops withdrawal; Entwicklungshilfe; Ausländisch; Entwicklungsfinanzierung; Abrüstung; Schock; Wirtschaftswachstum; Öffentlicher Haushalt; Afghanistan